2019
DOI: 10.3390/rs11182152
|View full text |Cite
|
Sign up to set email alerts
|

Airborne LiDAR Reveals a Vast Archaeological Landscape at the Nan Madol World Heritage Site

Abstract: An airborne LiDAR survey of the Nan Madol World Heritage Site and adjacent Temwen Island revealed a complex, irrigated cultivation system, the first found in the Central and Eastern Caroline Islands. This informs the goals of the sustainable conservation project, funded by the U.S. Department of State Ambassadors Fund for Cultural Preservation, that inspired the survey, and expands understanding of Nan Madol and its place in the network of Pacific island interaction and trade. Fieldwork verified the presence, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…This is particularly interesting, especially in light of the latest scientific advances in the fields of extra-terrestrial presence on Earth (Stranges 1996), ancient astronaut theory (AAT) 18 (cf. Comer et al 2019;Free 2014) and 18. As far back as 1896 already (cf.…”
Section: …And Then There Was Change and Bewildermentmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly interesting, especially in light of the latest scientific advances in the fields of extra-terrestrial presence on Earth (Stranges 1996), ancient astronaut theory (AAT) 18 (cf. Comer et al 2019;Free 2014) and 18. As far back as 1896 already (cf.…”
Section: …And Then There Was Change and Bewildermentmentioning
confidence: 99%
“…Regarding the latter, in the widely accepted publication edited by Joshua Free, called Necronomicon Anunnaki Bible, this particular group of suspected deities, as well as the mythological folklores and writings of the ancient Akkadians, Assyrians, Babylonians and Sumerians in which the Anunnaki regularly appear, are engaged with, explored and explained in light of the most recently available scientific research data. Finally, the results of their airborne LiDAR survey of the Nan Madol World Heritage Site, published by Comer et al (2019), have suggested that super-intelligent humans or other-worldly beings might, indeed, have been astrobiology (Malone, Drits-Esser & Stark 2014), to name but three examples. These are seriously challenging the basic cultural and ideological bias, as well as characteristic in-group versus out-group obsession inherent to all the major faith-based belief systems and their respective moral and ethical reservoirs across the globe at present.…”
Section: …And Then There Was Change and Bewildermentmentioning
confidence: 99%
“…However, the authors remark, "this distinct social action and display of resilience proved a temporary solution and ultimately the village was inundated and abandoned" (Galili et al, 2019, p. 1). The abandoned city of Nan Madol, a UNESCO World Heritage Site in the Federated States of Micronesia, includes a high-walled complex of nearly 100 artificial islands and canal system built atop a coral reef flat (McCoy et al, 2016;Comer et al, 2019). Nan Madol was a dynastic seat for several hundred years, into the 17th century; the technological means by which the complex was constructed remains unresolved (Pala, 2009).…”
Section: Questionsmentioning
confidence: 99%
“…However, there has been limited application of airborne lidar in the Small Island Developing States (SIDS) of the Pacific due to their remote geography and associated challenges. Airborne lidar has only been used in the archaeological contexts of the Pacific SIDS in American Samoa (Quintus, Day & Smith 2017), Tonga (Burley & Freeland 2022;Freeland et al 2016;Parton et al 2018), Vanuatu (Bedford, Siméoni & Lebot 2018), and Pohnpei (Comer et al 2019). In American Samoa, Vanuatu, and Pohnpei the lidar data revealed land modifications indicative of a complex irrigated cultivation system and agriculture production, while in Tonga defensive structures and pigeon trapping mounds were identified.…”
Section: Introductionmentioning
confidence: 99%